RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI GEREJA BETHEL INDONESIA BERBASIS WEB - Asmita Simanjuntak; Novri Adhiatma (Computer Science and Industrial Engineering, 2026)
The administration of church operations at GBI Shalom Piayu has historically relied on manual record-keeping, resulting in inefficiencies, data inconsistencies, and limited operational oversight. This study presents the design and implementation of a Church Information System aimed at optimizing the management of congregation data, church activities, tithes, and offerings. Employing the Waterfall development methodology, the research integrates systematic phases of requirement analysis, system design, coding, testing, and deployment. The system features online member registration, dynamic activity management, reporting, all centralized within a relational database. Performance evaluation indicates significant enhancements in operational efficiency: login is completed in under one second, member data entry requires seconds, and updates are processed within two seconds. The system substantially reduces manual workload, mitigates errors, and accelerates access to critical information. Future research is recommended to expand functionality to comprehensive financial management, advanced activity scheduling, and multi-platform accessibility via desktop and mobile applications. This study contributes a foundational framework for the digital modernization of church administration, promoting efficiency, accuracy, and scalability.